Safety and efficacy of once-weekly dulaglutide versus sitagliptin after 2years in metformin-treated patients with type 2 diabetes (AWARD-5): a randomized, phase III study - Weinstock, R S; Guerci, B; Umpierrez, G; Nauck, M A; Skrivanek, Z; Milicevic, Z (Diabetes, obesity & metabolism, 2015)
Aims To compare the once-weekly glucagon-like peptide-1 (GLP-1) receptor dulaglutide with the dipeptidyl peptidase-4 (DPP-4) inhibitor sitagliptin after 104weeks of treatment. Methods This AWARD-5 study was a multicentre, double-blind trial that randomized participants to dulaglutide (1.5 or 0.75mg) or sitagliptin 100mg for 104weeks or placebo (reported separately) for 26weeks. Change in glycated haemoglobin (HbA1c) concentration from baseline was the primary efficacy measure. A total of 1098 participants with HbA1c concentrations ≥7.0% (≥53.0mmol/mol) and ≤9.5% (≤80.3mmol/mol) were randomized, and 657 (59.8%) completed the study. We report results for dulaglutide and sitagliptin at the final endpoint. Results Changes in HbA1c at 104weeks were (least squares mean±standard error) -0.99±0.06% (-10.82±0.66mmol/mol), -0.71±0.07% (-7.76±0.77mmol/mol) and -0.32±0.06% (-3.50±0.66mmol/mol) for dulaglutide 1.5mg, dulaglutide 0.75mg and sitagliptin, respectively (p<0.001, both dulaglutide doses vs sitagliptin). Weight loss was greater with dulaglutide 1.5mg (p<0.001) and similar with 0.75mg versus sitagliptin (2.88±0.25, 2.39±0.26 and 1.75±0.25kg, respectively). Gastrointestinal adverse events were more common with dulaglutide 1.5 and 0.75mg versus sitagliptin (nausea 17 and 15% vs 7%, diarrhoea 16 and 12% vs 6%, vomiting 14 and 8% vs 4% respectively). Pancreatic, thyroid, cardiovascular and hypersensitivity safety were similar across groups. Conclusions Dulaglutide doses provided superior glycaemic control and dulaglutide 1.5mg resulted in greater weight reduction versus sitagliptin at 104weeks, with acceptable safety.